2020
DOI: 10.1038/s41422-020-00435-z
|View full text |Cite
|
Sign up to set email alerts
|

Mucus production stimulated by IFN-AhR signaling triggers hypoxia of COVID-19

Abstract: Silent hypoxia has emerged as a unique feature of coronavirus disease 2019 (COVID-19). In this study, we show that mucins are accumulated in the bronchoalveolar lavage fluid (BALF) of COVID-19 patients and are upregulated in the lungs of severe respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected mice and macaques. We find that induction of either interferon (IFN)-β or IFN-γ upon SARS-CoV-2 infection results in activation of aryl hydrocarbon receptor (AhR) signaling through an IDO-Kyn-dependent pathway, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 47 publications
3
99
0
Order By: Relevance
“…S6c, d ). Our previous study has shown that SARS-CoV-2 infection causes the production of mucus in the alveoli, thus aggravating the pathological damage 34 . Here, we found that the depletion of AMs relieved this mucous production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6c, d ). Our previous study has shown that SARS-CoV-2 infection causes the production of mucus in the alveoli, thus aggravating the pathological damage 34 . Here, we found that the depletion of AMs relieved this mucous production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the many pathways regulated by HSP90 chaperones includes the aryl hydrocarbon receptor (AhR) signalling pathway (Pongratz et al, 1992). During SARS-CoV-2 infection, AhR promotes interferon-induced mucus production in a rodent model (Liu et al, 2020). This build-up of alveolar mucus is thought to underly the obstructed blood-gas exchange seen in SARS-CoV-2 patients, thus leading to hypoxia and reduced lung capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Because AHR activity can be regulated by small molecules, AHR is an attractive target for therapeutic immunomodulation in the context of virus infection. Indeed, in pre-clinical models, AHR antagonists were shown to ameliorate ZIKV congenital syndrome in mice ( 106 ), increased survival in IAV infected mice ( 135 ) and reduce lung pathology induced by SARS-CoV-2 in hACE2-transgenic mice ( 136 ). However, clinical studies evaluating the safety and efficacy of targeting AHR for the treatment of viral infections are lacking.…”
Section: Therapeutic Modulation Of Ahr Activity In Clinical Practicementioning
confidence: 99%